The Comparison of Students Learning Result Based on Learning By Media and Learning by Video in Aljebra Concept - Muzakir, Ully; Salmina, Mik; Nasriadi, Ahmad; Fitriati, Fitriati; Sari, Intan Kemala; Rahmattullah, Rahmattullah; Ramazana, Ramazana (Teunuleh Publisher, 2023)
SMP Negeri 8 Banda Aceh has SPLDV learning media facilities and learning resources which are quite good, but the use of existing media and learning resources has not been utilized optimally which has an impact on student learning outcomes in mathematics. This study aims to determine what media is appropriate to use to motivate students in learning and increase student enthusiasm in learning. The research design used was True Experimental Design. The instrument used in data collection was a math comprehension test question. The application used to design video media is the SREEN O'MATIC. After the data was collected, it was analyzed using the T-Test. Based on the research results Calculated T-Value is 2.70 and T-Table Value is 1.70, this means is H1 accepted, so that H0 is rejected at a significant level ? = 0.05, it can be concluded that the teaching aids are better than video in SMP Negeri 8 Banda Aceh.